Action of snake venom components on the haemostatic system. - Hutton, R; Warrell, D (1993)
Among the components in snake venom are a number which have profound effects (either stimulatory or inhibitory) on haemostatic mechanisms, including coagulation, fibrinolysis, platelet function and vascular integrity. As a consequence, human victims of snakebite may suffer severe and sometimes fatal haemorrhagic and/or thrombotic sequelae. Many of these venom components have been isolated and their precise mechanisms of action established. Apart from direct fibrinolysins, procoagulants predominate, most of these exerting their effect late in the clotting cascade, activating factor X or prothrombin or directly converting fibrinogen to fibrin. Some of the procoagulants are, or have the potential to be, used as therapeutic agents. Some venom components have been put to use as laboratory reagents for diagnostic purposes or for characterising molecular defects of haemostasis, although because they often have unphysiological actions, results must be interpreted with caution. These and other useful constituents e.g. protein C activator and platelet aggregating agents are discussed.